Evaluation of the implementation of robotics curriculum at SMP IT Insan Sejahtera Sumedang - Destryana Riffandi; Rusman Rusman (Himpunan Pengembang Kurikulum Indonesia, 2026)
Robotics is an important aspect of technology that contributes to national competitiveness, so its introduction to students should be through education, including making it an intracurricular field in schools. This study aims to describe the evaluation of the implementation of the robotics curriculum at SMPIT Insan Sejahtera Sumedang. The study used a descriptive evaluation method with a case study design and a qualitative approach. It adopted the CIPP evaluation model, which is limited to input, process, and product components. Research participants included the principal, vice principal, robotics teacher, and grade IX students. Data collection was conducted through semi-structured interviews. The results of the study indicate that the implementation of the robotics curriculum is running quite optimally, especially in terms of learning outcomes that meet the evaluation criteria. However, there are still several weaknesses in the input aspect, such as teacher competence, facilities and infrastructure, and monitoring of learning outcomes, as well as in the process aspect, related to the selection of learning methods that are not fully appropriate. Based on these findings, it can be concluded that although the implementation of the robotics curriculum has shown good results, improvements are needed in support and learning strategies to achieve a more effective and optimal implementation. Abstrak Robotika merupakan aspek penting dalam bidang teknologi yang berperan dalam meningkatkan daya saing bangsa, sehingga pengenalannya kepada murid perlu dilakukan melalui pendidikan, salah satunya dengan menjadikannya sebagai bidang intrakurikuler di sekolah. Penelitian ini bertujuan untuk mendeskripsikan evaluasi implementasi kurikulum robotika di SMPIT Insan Sejahtera Sumedang. Penelitian menggunakan metode evaluasi deskriptif dengan desain studi kasus dan pendekatan kualitatif, serta mengadopsi model evaluasi CIPP yang dibatasi pada komponen input, proses, dan produk. Partisipan penelitian meliputi kepala sekolah, wakil kepala sekolah, guru robotika, dan murid kelas IX. Teknik pengumpulan data dilakukan melalui wawancara semi-terstruktur. Hasil penelitian menunjukkan bahwa implementasi kurikulum robotika berjalan cukup optimal, terutama pada aspek hasil pembelajaran yang telah memenuhi kriteria evaluasi. Namun demikian, masih terdapat beberapa kelemahan pada aspek input, seperti kompetensi guru, sarana dan prasarana, pengawasan capaian pembelajaran, serta pada aspek proses terkait pemilihan metode pembelajaran yang belum sepenuhnya sesuai. Berdasarkan temuan tersebut, dapat disimpulkan bahwa meskipun pelaksanaan kurikulum robotika telah menunjukkan capaian yang baik, diperlukan peningkatan pada aspek pendukung dan strategi pembelajaran agar implementasinya lebih efektif dan optimal. Kata Kunci: evaluasi kurikulum; integrasi teknologi; pendidikan menengah; pendidikan robotika